The Impact of Cognitive Skill, and Individual Innovativeness on Digital Formal Learning Mediated by Attitude to Use Interactive Worksheet Digital - Dessy Seri Wahyuni; Gede Ariadi (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2022)
This research explores the essence of cognitive skill and individual innovativeness in junior high school students in Bali Province, influencing digital formal learning across a mediator variable. This study proposes to provide the comprehension of digital technology used by students that focus on attitude to use interactive worksheet digital as a mediator for supporting digital formal learning. The study analyzes sampling data from 167 students in the junior high school in Buleleng Regency by partial least square-path modeling. The findings reveal that cognitive skill and individual innovativeness in digital formal learning are partially mediated by attitude to digitally using interactive worksheets. The finding discovers students’ attitudes toward using digital tools that enhance their output, such as accomplishing tasks more effectively and delivering satisfying learning.